Doomsday [videorecording (Blu-Ray)] - Paul, Steven; Carver, Benedict; Marshall, Neil, 1970-; Mitra, Rhona, 1976-; Hoskins, Bob; Lester, Adrian; O'Hara, David, 1965-; McDowell, Malcolm, 1943- (Universal Studios Home Entertainment, 2008)
A lethal virus spreads throughout Great Britain, infecting millions and killing hundreds of thousands. To contain the threat the government evacuates as many survivors as it can out of the infected area and the rest of the country succumbs to fear and chaos. The quarantine is successful. Three decades later, the Reaper Virus violently resurfaces. An elite group of specialists, including Eden Sinclair, is urgently dispatched into the still-quarantined country to retrieve a cure by any means necessary. Shut off from the rest of the world, the unit must battle through a landscape that has become a waking nightmare.